Improving efficiency in public financial management a study on the adoption of the Unified Account Code Structure (UACS) in select national government agencies - Quilinguing, Agnes Kristine Aranza (National College of Public Administration and Governance, University of the Philippines Diliman, 2019)
The Philippine government has been implementing the Unified Account Code Strucure (UACS) as an integral component of the Public Financial Management (PFM) Reform Program since 2014. It is meant to simplify, improve, and harmonize government's financial management process and information systems. Through UACS, oversight and implementing agencies share a common set of financial data and information , from budgeting and cash management to accounting and audit. The use of codes help simplify and consolidate formats for financial reports; facilitates timely and accurate reporting of actual receipts and expenditures agaisnt programmed revenues and expenditures; and enables comparison of disbursements for programs, projects, and activities with their approved appropriations.